(untitled) (Sciences & Technology. A, exactes sciences, 2014)
CuBi2O4/CeO2 composite materials were synthesized by solid state method and were characterized by a number of techniques such as X-ray diffraction, scanning electron microscopy and UV–Vis diffuse reflectance spectroscopy. The photocatalytic activity of the materials was investigated under UVA light and assessed using Congo red (CR) dye as probe reaction. The CuBi2O4/CeO2 photocatalyst exhibited the high efficiency as a result of 83.05% of decomposition of CR for 100 min of irradiation time with 30 wt % of CuBi2O4 at room temperature and a pH 7. The photodegradation reactions were satisfactory correlated with the pseudo-first-order kinetic model. The mechanism of the enhanced photocatalytic efficiency was explained by the heterojunction charge separation model.